Bayesian analysis of quark spectral properties from the Dyson-Schwinger equation - Fischer, Christian S.; Pawlowski, Jan M.; Rothkopf, Alexander (Arxiv, 2017)
We report results on the quark spectral function in the Landau gauge at finite temperature determined from its Dyson-Schwinger equation. Compared to earlier quenched results this study encompasses unquenched $N_f=2+1$ fermion flavors in the medium. For the reconstruction of real-time spectra we deploy a recent Bayesian approach (BR method) and develop a new prior in order to better assess the inherent systematic uncertainties. We identify the quark quasi-particle spectrum and analyze the (non-)appearance of zero modes at or around the pseudo-critical temperature. In both, the fully unquenched system and a simpler truncation using a model for the gluon propagator we observe a characteristic three-peak structure at zero three-momentum. The temperature dependence of these structures in case of the gluon propagator model is different than observed in previous studies. For the back-coupled and unquenched case we find interesting modifications at and around the pseudo-critical transition temperature.